Pre-exposure prophylaxis access, uptake and usage by young people: a systematic review of barriers and facilitators - Sarah Warzywoda; James A. Fowler; Amalie Dyda; Lisa Fitzgerald; Amy B. Mullens; Judith A. Dean (Therapeutic Advances in Infectious Disease)
Background: Young people’s sexual health decision-making, including decisions to access and adhere to HIV prevention strategies such as Pre-Exposure Prophylaxis (PrEP), are influenced by a range of internal and external factors. Synthesizing these factors is essential to guide the development of youth-focused PrEP health promotion strategies to contribute to international goals of ending HIV transmission. Objective: To understand the individual, interpersonal, sociocultural and systemic barriers and facilitators to PrEP access, uptake and use experienced by young people 24 years and younger. Design: A systematic review that adhered to the Preferred Reporting Items of Systematic Review and Meta-Analysis Protocols. Data Sources and Methods: Eight databases (PubMed, Scopus, Cochrane, Medline, CINAHL, JBI, EMBASE, Web of Science) were systematically searched using terms related to young people, HIV and PrEP use. A narrative synthesis approach was used to delineate key barriers and facilitators to PrEP access, uptake and use. Results: Of 11,273 returned articles, 32 met the eligibility criteria for inclusion: 18 from the United States, 10 from African nations and two from Brazil. Barriers and facilitators to PrEP access, uptake and use experienced by young people were identified across intrapersonal, interpersonal, community and systems levels. These factors are described under four overarching themes that relate to knowledge, side effects and perceptions of risk; attitudes and perceptions of family and partners; community attitudes and stigma; and negative healthcare provider experiences and difficulties navigating complex costly healthcare systems. Conclusion: Findings suggest individual-level factors need consideration alongside the impacts of healthcare systems and broader systemic sociocultural structures within young people’s relationships when developing PrEP health promotion strategies and services. Without considering these wider external implications to access, uptake and use of PrEP, global targets towards the elimination of HIV transmission will likely remain out of reach. Registration: This review was registered with Prospero (CRD42022296550).